Analysis of Tensile Strength and Percent Elongation of Edible Composite Film from Milkfish Bone Gelatin and Red Algae Carrageenan - Rr. Radipta Lailatussifa; Ahmad Jibril; Nur Hidayah; Rufnia Ayu Afifah; Siluh Putu Sri Dia Utari; Fenny Crista Anastasia Panjaitan; Indra Kristiana (Dinasti International Journal of Education Management And Social Science, 2025)
This research aims to develop an innovative solution to reduce the problem of plastic waste by designing and optimizing an edible film formula using milkfish bone gelatin and red algae as edible film composite materials. Milkfish gelatin was chosen because it can form an elastic and strong film, while red algae provides softness and resistance to microorganism activity. This research consists of several stages, including gelatin extraction, carrageenan extraction from Eucheuma cottonii and formulating composite edible films. Based on the results of the analysis carried out, the average yield of milkfish bone gelatin was 10.55% and the average yield of E.cottonii carrageenan extract was 20.62%. The thickness of composite edible film ranges from 0.15-0.25 mm, the highest tensile strength value is 6.3 MPa and the lowest is 3 MPa, and the highest percent elongation of edible film is 80% and the lowest is 36.67%. The values ??obtained are in accordance with the JIS 2-1707 (Japan Industrial Standard) (1946) standard.